Rhetorical Implications of the Chinese Detaineesâ€™ Ghostly Poems at Angel Island: Lonely Voices, Alien Discourse, and Collective Identity - Zhao, Heping (Richtmann Publishing, 2012)
February 15th, 2009, saw the reopening of the Angel Island Immigration Station in San Francisco as a museum thatshowcases the sufferings of imprisoned Chinese immigrants who came to the west coast of the United States of America during the firsthalf of the 20th century. Although many travelers or immigrants from East Asian countries and the eastern part of Russia were detainedand roughed up when they arrived in San Francisco, by far the majority of the detainees were Chinese. Under the notoriouslydiscriminating law known as â€œChinese Exclusion Actâ€ passed in 1882 and repealed in 1943, no fewer than 120,000 Chinese were held inAngel Island against their will between 1910 and the early 1940â€™s, some of them for as long as two years. Different from their fellowdetainees from Japan, Korea, or Russia, who registered their frustration and anger vocally or in short pieces of writing, the Chinese whowere confined in Angel Island wrote poems instead and carved them on the walls of their bunk barracks. These poems, totaling over150 and all written in Chinese, recorded a range of feelings the detainees experienced: fear, uncertainty, despair, loneliness,homesickness, indignation, defiance, and even contempt. In my presentation, I would like to categorize some of these poems by theirthemes, identify the emotions expressed in them, and analyze their structural patterns in the Chinese poetic discursive tradition. In sodoing, I intend to establish a link among all these individual works of poetry written and inscribed in times of great distress and see how,as a very alien form of rhetorical practice to the average American reader, each of these poems contributed to the collective identity ofChinese emigrants to America in the early 20th century.